(untitled) (Bangladesh Journal of Pharmacology, 2016)
Our objective was to evaluate an open-label, multicenter, single-arm study to appraise whether amrubicin therapy improves patients with refractory small-cell lung cancer in Chinese clinical study. Patients (n=95) with refractory small-cell lung cancer received 3 consecutive days amrubicin therapy for 21 days. Overall response rate of response to amrubicin was 39%. Anemia, febrile neutropenia, thrombocytopenia, hyperglycemia, hyponatremia, infection, elevated serum transaminases levels were appeared, but the incidences of adverse events were very few. Our results suggest amrubicin therapy can improve patients with refractory small-cell lung cancer and may be an effective and safe treatment option.